Climate change challenges in central banking: A systematic review with bibliometric and content analysis - Ahmad Kaab Omeir; Deimante Vasiliauskaite (Banks and Bank Systems)
Solving climate change issues has become the most essential topic in all areas of business and activity. Even central banks take action to enhance climate risk management. Central banks are taking action to regulate the financial system and manage foreign reserves by implementing green investments in their own and monetary portfolios, thereby utilizing their direct functions. This paper aims to identify the primary areas of focus for central banks in climate risk management by systematically reviewing and consolidating existing scientific papers, identifying research gaps, and highlighting areas that require further investigation. Using bibliometric and content analysis, the study examines the primary areas in which central banks can contribute to addressing climate change challenges. Using Web of Science data in this research, 503 English-language articles on “climate risk” were analyzed, and the scope was then narrowed by analyzing articles using the keywords “climate risk banks,” which limited the research area to 320 articles. The analysis reveals that central banks are increasingly integrating climate risk management into their policy frameworks, employing stress tests and disclosure guidelines to enhance the resilience of financial institutions. The findings reveal a significant gap in scientific research on the role of central banks in climate risk mitigation through foreign reserve management, despite their primary responsibility for managing climate risks within the banking system. This study underscores the necessity for enhanced risk assessment methodologies and collaborative regulatory efforts, thereby advancing the scientific discourse and informing the development of practical policies.